OCORRÊNCIA DE ANTICORPOS ANTI-TOXOPLASMA GONDII E ANTI-LEPTOSPIRA SPP. EM SUÍNOS ABATIDOS EM TRÊS ABATEDOUROS DOS ESTADOS DE MINAS GERAIS E SÃO PAULO - Pezerico, G.b.; Pezerico, S.b. [UNESP]; Silva, R.c.; Hoffmann, J.l. [UNESP]; Camargo, L.b. [UNESP]; Langoni, H. [UNESP] (Instituto Biológico, 2022)
Many seroepidemiological inquiries of toxoplasmosis and leptospirosis in swine have been realized in many Brazilian states, demonstrating the importance of these diseases for swine farming, as well as the potential of this swine species as a source of infection of these diseases for man. This study aimed to establish the occurrence of antibodies anti-Toxoplasma gondii and anti-Leptospira spp. in swine slaughtered in 3 slaughterhouses, located in Minas Gerais and São Paulo states, Brazil. Two hundred sixty-two blood samples were collected from slaughtered swine, from 16 cities, and the sera samples were submitted to the modified agglutination test, to investigate antiT. gondii antibodies, and to the microscopic agglutination test, to investigate anti-Leptospira spp. antibodies. No sample was positive for T. gondii, and 2 samples reacted to Leptospira interrogans, serovar Pyrogenes (titer 100). These low occurrences of antibodies in the studied swine, for the Leptospiratest, could be due the use of the system of total confinement, allied to the hygienic-sanitary swine management and the slaughtered animals’ short length of stay at the farms.

Diversos inquéritos soroepidemiológicos a respeito da toxoplasmose e leptospirose em suínos foram realizados em diferentes estados brasileiros, demonstrando a importância destas enfermidades para a suinocultura, bem como o potencial da espécie suína como fonte de infecção destas enfermidades para o homem. Este trabalho objetivou estabelecer as ocorrências de anticorpos anti-Toxoplasma gondii e anti-Leptospira spp. em suínos abatidos em três abatedouros, situados nos Estados de Minas Gerais e São Paulo. Foram colhidas 262 amostras de sangue de suínos terminados, provenientes de 16 municípios. Os soros foram submetidos ao método de Aglutinação Direta Modificada (MAD) para pesquisa de anticorpos anti-T. gondii, e à Soroaglutinação Microscópica (SAM), para anticorpos anti-Leptospira spp. Nenhuma amostra foi positiva para T. gondii e duas amostras reagiram para Leptospira interrogans, sorovar Pyrogenes (título 100). Os resultados devem ser em função do emprego do sistema de confinamento total, aliado ao manejo higiênico-sanitário na atividade suinícola e pelo pequeno período de permanência dos animais terminados nas granjas.
OCCURRENCE OF ANTIBODIES ANTI-TOXOPLASMA GONDII AND ANTI-LEPTOSPIRA SPP. IN SWINE SLAUGHTERED IN THREE SLAUGHTERHOUSES OF MINAS GERAIS AND SÃO PAULO STATES, BRAZIL
Keywords: Toxoplasmosis; leptospirosis; swine; serodiagnosis; slaughterhouse; Toxoplasmose; leptospirose; suíno; sorodiagnóstico; abatedouro